Development of Animated Video Media Material of Fusion Food For Culinary Expertise Students (SMKN 3 Tangerang) - Anandita Indira Hayat; Yeni Yulianti; Mahdiyah Mahdiyah (Jurnal Ilmiah Mandala Education (JIME), 2025)
The purpose of this study is to develop and assess the feasibility of animated video learning media for fusion food material for Culinary expertise students at SMKN 3 Tangerang. This research is a type of Research & Development research with a 4D model. Data collection techniques used observation, interviews, and questionnaires. The results of the study showed that the validation of the material expert's assessment obtained an average of 79.23% with the category of Feasible. The media expert's assessment obtained an average of 78.66% with the category of Feasible. And the language expert's assessment obtained an average of 86.66% with the category of Very Feasible. While the results of the initial field trial obtained an average of 78.60% with the category of Feasible, the results of the small group trial obtained an average of 83.37% with the category of Feasible, and the large group trial obtained an average of 88.67% with the category of Very Feasible. The assessment of the user response test results obtained an average of 97.78% with the category of Very Interested. It can be concluded that the development of animated video media for fusion food material for culinary expertise students (SMKN 3 Tangerang) is declared suitable to be used as a learning resource.